Synthesis of visible light responsive ZnCoFe layered double hydroxide towards enhanced photocatalytic activity in water treatment - Keyikoglu, Ramazan; Dogan, Irmak Naz; Khataee, Alireza; Orooji, Yasin; Kobya, Mehmet; Yoon, Yeojoon (Pergamon-Elsevier Science Ltd, 2022)
In this study, a ternary layered double hydroxide containing Zn, Co, and Fe transition metals (ZnCoFe LDH) was developed using a co-precipitation procedure. The as-synthesized photocatalyst was evaluated for its perfor-mance in the degradation of methylene blue (MB) under visible light irradiation. The effects of various process conditions including photocatalyst dosage, pollutant concentration, pH, lamp distance, and lamp power were investigated. The ZnCoFe LDH achieved approximately 74% photodegradation efficiency owing to the narrow bandgap of 2.14 eV. The Langmuir-Hinselwood rate constants were calculated as 1.17 min-1 and 3.55 min-1 for photolysis by LED lamp alone and for photocatalysis by LED/ZnCoFe LDH, respectively. The photocatalytic ability of the LDH was attributed to the generation of radical species like center dot OH and O2 center dot-. The photocatalytic degradation intermediates of MB were determined by GC-MS analysis. The catalyst retained its performance throughout seven reuse cycles with only a 4.17% reduction in removal efficiency. The energy per order EEO of the ZnCoFe/LED process in 180 min treatment time was determined as 5.41 kWh.m- 3. order-1. This study shows that ZnCoFe LDH has sufficient activity and photostability for long-term application in photocatalytic water treatment.
Keywords: Hydrotalcite; Electrical energy per order; Methylene blue; Photocatalyst; Pollutant degradation